2022
DOI: 10.21037/atm-21-6145
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of transient receptor potential channels in ocular diseases: a narrative review

Abstract: Background and Objective: Transient receptor potential (TRP) channels are a superfamily of functionally diverse and widely expressed cation channels which exhibit complex regulatory patterns and sensitivity to multiple environmental factors. The involvement of these ion channels is critical in various physiological functions and pathophysiological conditions. In recent decades, a growing number of studies have identified the essential role that TRP channels play in many ocular diseases. In this study, we perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 218 publications
(267 reference statements)
0
16
0
1
Order By: Relevance
“…In the keyword clustering analysis encompassing original studies and reviews, DR has emerged as a significant focus of current investigations. As a critical complication of diabetes, DR poses a substantial risk of visual impairment and blindness, exhibiting severity ranging from non-proliferative DR to proliferative DR ( 62 , 63 ). Moos et al ( 64 ) have demonstrated that PMX500FI, a novel synthetic derivative of α-lipoic acid, exhibits the ability to activate the NRF2 signaling pathway and mitigate oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…In the keyword clustering analysis encompassing original studies and reviews, DR has emerged as a significant focus of current investigations. As a critical complication of diabetes, DR poses a substantial risk of visual impairment and blindness, exhibiting severity ranging from non-proliferative DR to proliferative DR ( 62 , 63 ). Moos et al ( 64 ) have demonstrated that PMX500FI, a novel synthetic derivative of α-lipoic acid, exhibits the ability to activate the NRF2 signaling pathway and mitigate oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the consensus pervades that DR represents an ocular malady characterized by aberrations within the microvascular and neural frameworks. Prominently, the pathological spectrum encompasses non-proliferative and proliferative manifestations ( 8 , 9 ), all of which commence with the dysfunction of the blood-retina barrier ( 10 , 11 ). The cardinal facets of microangiopathy encompass the perturbation of endothelial cells and pericyte architecture, while neuropathy predominantly culminates in neuronal demise ( 8 , 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…Prominently, the pathological spectrum encompasses non-proliferative and proliferative manifestations ( 8 , 9 ), all of which commence with the dysfunction of the blood-retina barrier ( 10 , 11 ). The cardinal facets of microangiopathy encompass the perturbation of endothelial cells and pericyte architecture, while neuropathy predominantly culminates in neuronal demise ( 8 , 9 ). Non-proliferative diabetic retinopathy (NPDR) chiefly materializes through escalated vascular permeability, engendering the ingress of substantial volumes of fluid, lipid peroxides, and an array of inflammatory mediators into the retinal milieu, thereby provoking macular edema.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations